Pengetahuan Remaja tentang Generasi Berencana (GenRe) melalui Kearifan Lokal - Ardi Saputra; Dian Sri Andriani; Azizah Husin; Silvia AR; Rizky Ghoffar Ismail (ABDIMASY: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
Coaching for adolescents can be initiated through knowledge of future challenges, both in personal life and in socializing. This study aims to determine the knowledge of adolescents about Generation Planning (GenRe) through the values ​​of local wisdom. The research was conducted at a senior high school in Kecamatan Tanah Abang, Kabupaten Penukal Abab Lematang Ilir with the research subjects being high school students who were selected by random sampling technique. Data were collected through questionnaires on knowledge of reproductive health, drugs and addictive substances, as well as local wisdom. The results showed that 68.33% of students knew enough about reproductive health, 80% of students knew well about drugs and addictive substances and their consequences, and only 50.40% of students knew and practiced the values ​​of local wisdom in everyday life. Based on the results of the study, students' knowledge regarding Generation Planning is included in the sufficient category so that it is necessary to inculcate the values ​​of local wisdom and socialize Generation Planning by parents, teachers, and community leaders in order to create a golden generation in the future.